The Arena: An indoor mixed reality space - Dias, J. M. S.; Bastos, R.; Santos, P.; Monteiro, L.; Canhoto, J. (Interacção 2004 - 1ª Conferência Nacional em Interacção Pessoa-Máquina, 2021)
ln this paper, we introduce the Arena, an indoor space for mobile mixed reality interaction. The Arena includes a new user tracking system appropriate for AR/MR applications and a new Too/kit oriented to the augmented and mixed reality applications developer, the MX Too/kit. This too/kit is defined at a somewhat higher abstraction levei, by hiding from the programmer low-level implementation details and facilitating ARJMR object-oriented programming. The system handles, uniformly, video input, video output (for headsets and monitors), sound aurelisation and Multimodal Human-Computer Interaction in ARJMR, including, tangible interfaces, speech recognition and gesture recognition.